Guide to Modeling and Simulation of Systems of Systems User$1 (Bs Reference /s - Zeigler, Bernard P.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
This user$1 (Bs reference is a companion to the separate book also titled (3z(BGuide to Modeling and Simulation of Systems of Systems.(3y (BThe principal book explicates integrated development environments to support virtual building and testing of systems of systems, covering in some depth the MS4 Modeling Environment$1!"(B. This user$1 (Bs reference provides a quick reference and exposition of the various concepts and functional features covered in that book. The topics in the user$1 (Bs reference are grouped in alignment with the workflow displayed on the MS4 Modeling Environment$1!" (Blaunch page, under the headings Atomic Models, System Entity Structure, Pruning SES, and Miscellaneous. For each feature, the reference discusses why we use it, when we should use it, and how to use it. Further comments and links to related features are also included.s
Atomic Models List -- System Entity Structure List -- Pruning SES List -- Miscellaneous List.
Keywords: Computer science; Computer simulation; Computer Science; Simulation and Modeling